Characteristics Of Dikes In Kinta Valley, Perak Using Geophysical And Geologial Approaches - Tajuddin, Muhammad ‘Izzat ‘Irfan Ahmad (2021)
Simpang Pulai formation is part of Kinta Valley Perak where this area was well-known for its rigorous tin mining activity and production in the 19th century. The extraction of different minerals from the mining is commonly used in various industries like manufacturing and construction. Due to the existence of various rock types and different geological structures, it shows that this area is rich in mineral resources which makes this industry the main economic activity in Perak state. Different minerals were explored and operated by different companies, but there was no proper exploration by using geophysical methods prior to using human ability. Due to different geological structures formed in this area, two different dikes were found in the quarry that is still being operated by Imerys Mineral Sdn Bhd and the origin of this formation still remains unidentified. This research focuses on using remote sensing as one of the geophysical method in explaining the surface structures present in this formation. The outcrop and mapping studies were performed by using remote sensing images that were interpreted and captured by ArcGIS and Lidar mapping software by using object based image analysis (OBIA). Elevation and vegetation distribution were mapped and it was discovered that Simpang Pulai area is still unexplored and filled with hills and valleys. The elevation distribution in the mining area ranges between 150m to 500m above sea level. Meanwhile, the mineralogy of the rocks were distinguished by performing four different lab studies which are XRD, EDX, SEM and thin section analysis. Different rock samples were taken from this area while doing physical observation. The different lab studies such as XRD, EDX, SEM and thin section analysis were used to identify and observe the chemical and physical properties on each of the rock samples. As for the outcome, the first dike mainly consists of quartz mineral and the second dike was composed with different minerals such as silicon, quartz, aluminum, and feldspar. Both dikes have different mineral, physical and chemical properties compared to the host rock. This is because the dikes were formed later as the host rock was intruded in the existing formation. Thus, both of dikes are magmatic dike because they were mainly made by igneous rock type. First dike was composed by quartz mineral forming quartz dike and second dike was composed with major minerals from igneous rock forming granite dike. The mineral composition for both dikes are the mineral resources for the operating companies in the Kinta Valley area. Even-though the remote sensing data obtained was limited, physical study was carried out in order to obtain additional information on the mineral exploration with the aim to determine the suitable method to perform excavation and extraction.